Peran Majlis Reboan Agung dalam Membina Spiritualitas Jamaah di Yayasan Pesantren Ahlus-Shafa Wal-Wafa - Siti Wikoyatul Widiah; Anisa Anisa; Ihya Ulumuddin (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2026)
Reboan Agung at the Ahlus Shafa Wal Wafa Islamic Boarding School is a recitation tradition that is carried out regularly every Wednesday and Thursday evenings. This activity began in 2002 from a simple recitation led by KH. Mohammad Nizam As-Shofa, who at that time was only followed by a few people, especially his family members. Over time, this study developed into a large spiritual community and served as an important place to instill the values of Sufism and Islamic spirituality to the students and their congregation. This research aims to analyze the role of Majlis Reboan Agung in supporting the spirituality of the congregation within the Ahlus Shafa Wal Wafa Islamic Boarding School Foundation. The research method used is qualitative with a case study approach. The research results show that Majlis Reboan Agung has a very important role in supporting the spirituality of the congregation. Many congregants felt calm, motivated, and experienced positive changes such as increased patience, sincerity, surrender, enthusiasm, and determination in facing life's trials. They apply these values in their daily lives, which have an impact on ego control, self-understanding, and better relationships with other people. These findings show that Reboan Agung functions as an effective means for cultivating spirituality, not only increasing religious knowledge, but also forming character, strengthening ukhuwah, and growing the congregation's commitment to consistently practicing Islamic teachings.